PENGARUH MODEL PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Novia Nurrizka; Pramonoadi Pramonoadi (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2018)
The purpose of this research is to know the influence of a model of learning math realistic against the problem solving math students of the material himpunan seven grade class in Junior High School 1 Driyorejo. The method was used experiment with research design the posttest-only control design. The population of this study were seven grade students at Junior High School 1 Driyorejo, where as the sample was seven grade J as experiment class and seven G as control class. The instrument test which is given in this research consisted of 5 quations of esay typed. Data analysis using t-test of both groups obtained ttest of 2,42, while ttable of 2,0017. Because 2,42 > 2,0017 so > , is appropriate with hypothesis which is submitted in this research H0 is refused that meant there is influence of a model of learning math realistic against the problem solving math students of the material himpunan seven grade class in Junior High School 1 Driyorejo. Keywords: model of learning math realistic, problem solving math.